Development of AI-based interactive digital modules to enhance innovation in economics learning - Dwi Herlindawati; Irmadatus Sholekhah; Sri Kantun; Titin Kartini; Tiara Tiara (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
Rapid technological advancements in the digital era require teachers to continuously innovate in selecting effective learning media. Artificial intelligence (AI) offers new opportunities to enhance instructional quality through more adaptive, interactive, and personalized digital learning resources. This study aims to develop and evaluate an AI-based interactive digital module for senior high school economics instruction. Employing a research and development (R&D) approach with the ADDIE model — Analysis, Design, Development, Implementation, and Evaluation — the study conducted expert validations and large-scale trials involving five economics teachers and 158 Grade XI students across five public senior high schools in Jember Regency. The module was assessed using five core criteria of e-module quality. Results show that the module achieved excellent ratings across all categories: self-instruction (96.36%), self-contained (96%), stand-alone (94.10%), adaptive (99.66%), and user-friendly (97.36%), with an overall average score of 96.70%. These findings indicate that the AI-based interactive module is highly feasible and effective for supporting economics learning, addressing the limitations of conventional instructional materials, and aligning with the demands of digital learning in the Industrial Revolution 4.0 era. The study concludes that the developed module can serve as a valuable instructional innovation for economics teachers, enhancing both learning engagement and the quality of technology-integrated education.